2017
DOI: 10.1177/2053168017713059
|View full text |Cite
|
Sign up to set email alerts
|

The general error correction model in practice

Abstract: Enns et al. respond to recent work by Grant and Lebo and Lebo and Grant that raises a number of concerns with political scientists' use of the general error correction model (GECM). While agreeing with the particular rules one should apply when using unit root data in the GECM, Enns et al. still advocate procedures that will lead researchers astray. Most especially, they fail to recognize the difficulty in interpreting the GECM's "error correction coefficient." Without being certain of the univariate propertie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 36 publications
(123 reference statements)
0
20
0
Order By: Relevance
“…Our other series have time dependence-that is, the mobility in a city on a given day will be highly correlated with mobility in that city on adjacent days-but the extent to which this is present varies from city to city. While properly diagnosing the properties of each time series for each city would allow us to choose among various modeling options, the relatively short time span in our data makes it diffi cult to rely on tests of stationarity ( Lebo and Kraft 2017 ).…”
Section: Modeling the Policy-mobility Relationshipmentioning
confidence: 99%
“…Our other series have time dependence-that is, the mobility in a city on a given day will be highly correlated with mobility in that city on adjacent days-but the extent to which this is present varies from city to city. While properly diagnosing the properties of each time series for each city would allow us to choose among various modeling options, the relatively short time span in our data makes it diffi cult to rely on tests of stationarity ( Lebo and Kraft 2017 ).…”
Section: Modeling the Policy-mobility Relationshipmentioning
confidence: 99%
“…If there is no cointegration, it is possible to apply vector autoregression models in the first differences. In the presence of cointegration of time series, error correction models (Lebo and Kraft, 2017) and vector autoregressive models at levels (Ren, et al, (2013) are used. Based on the official report of the Regulator, the primary set of indicators characterizing the state of the insurance market of Ukraine has been formed.…”
Section: Marketing and Management Of Innovations 2019 Issuementioning
confidence: 99%
“…That paper showed that much political science research (including some of our own) incorrectly interpreted De Boef and Keele (2008) to imply that the general error correction model (GECM) was more flexible than it is and we emphasized that using the correct MacKinnon critical values was an important part of cointegration tests when estimating the GECM with nonstationary series (also see Enns et al, 2016). Those insights remain essential points of agreement that Lebo and Kraft (2017) identify. 2.…”
Section: Notesmentioning
confidence: 97%